Cerebral Cortical Microinfarcts on Magnetic Resonance Imaging and Their Association With Cognition in Cerebral Amyloid Angiopathy. Issue 10 (October 2018) - Xiong, Li; van Veluw, Susanne J.; Bounemia, Narimene; Charidimou, Andreas; Pasi, Marco; Boulouis, Gregoire; Reijmer, Yael D.; Giese, Anne-Katrin; Davidsdottir, Sigurros; Fotiadis, Panagiotis; Valenti, Raffaella; Riley, Grace; et al.
Abstract : Background and Purpose—: We aimed to explore the association between presence of cerebral cortical microinfarcts (CMIs) on magnetic resonance imaging and other small-vessel disease neuroimaging biomarkers in cerebral amyloid angiopathy (CAA) and to analyze the role of CMIs on individual cognitive domains and dementia conversion. Methods—: Participants were recruited from an ongoing longitudinal research cohort of eligible CAA patients between March 2006 and October 2016. A total of 102 cases were included in the analysis that assessed the relationship of cortical CMIs to CAA neuroimaging markers. Ninety-five subjects had neuropsychological tests conducted within 1 month of magnetic resonance imaging scanning. Seventy-five nondemented CAA patients had cognitive evaluation data available during follow-up. Results—: Among 102 patients enrolled, 40 patients had CMIs (39%) on magnetic resonance imaging. CMIs were uniformly distributed throughout the cortex without regional predilection ( P =0.971). The presence of CMIs was associated with lower total brain volume (odds ratio, 0.85; 95% CI, 0.74–0.98; P =0.025) and presence of cortical superficial siderosis (odds ratio, 2.66; 95% CI, 1.10–6.39; P =0.029). In 95 subjects with neuropsychological tests, presence of CMIs was associated with impaired executive function (β, −0.23; 95% CI, −0.44 to −0.02; P =0.036) and processing speed (β, −0.24; 95% CI, −0.45 to −0.04; P =0.020). Patients with CMIs had a higher cumulative dementia incidence compared with patients without CMIs ( P =0.043), whereas only baseline total brain volume (hazard ratio, 0.76; 95% CI, 0.62–0.92; P =0.006) independently predicted dementia conversion. Conclusions—: Magnetic resonance imaging–detected CMIs in CAA correlated with greater overall disease burden. The presence of CMIs was associated with worse cognitive performance, whereas only total brain atrophy independently predicted dementia conversion. Abstract : Supplemental Digital Content is available in the text.